Encapsulation of Lithium Vanadium Phosphate in Reduced Graphene Oxide for a Lithium-ion Battery Cathode with Stable Elevated Temperature Performance. (1st November 2017) - Lim, Chek Hai; Jung, Young Hwa; Yeom, Su Jeong; Lee, Hyun-Wook; Kim, Do Kyung
Abstract: Polyanion-type cathode materials have received considerable attention for lithium-ion battery applications because of their excellent thermal stability compared to oxide compounds. Although the incorporation of carbonaceous materials can augment the cycling performance, the role of carbon structures in lithium vanadium phosphate (Li3 V2 (PO4 )3, LVP) compounds remains unclear at an elevated temperature. Herein, carbon-coated Li3 V2 (PO4 )3 (C-LVP) and reduced-graphene-oxide-wrapped Li3 V2 (PO4 )3 (rGO-LVP) samples are prepared, their electrochemical performance is examined at room temperature and an elevated temperature. The rGO-LVP and C-LVP samples exhibit discharge capacities of ∼131 mAh g −1 and ∼124 mAh g −1, respectively, at charge and discharge rates of 10C in the range of 3.0–4.3 V at 55 °C after cycling at various rates. The capacity retentions of the rGO-LVP and C-LVP samples are ∼95% and ∼85%, respectively, after 150 cycles at charge and discharge rates of 1C in the range of 3.0–4.3 V at 55 °C. The excellent rate performance and cycling stability of the rGO-LVP sample are due to its capability in maintaining a low charge transfer resistance or a higher electrical conductivity and ionic conductivity as compared to the C-LVP sample during electrochemical cycling, as demonstrated by electrochemical impedance spectroscopy and cyclic voltammetry. The results have provided essential insight into designing inorganic–carbon hybrid materials for future batteries.